Neddylation Facilitates the Antiviral Response in Zebrafish - Yu, Guangqing; Liu, Xing; Tang, Jinhua; Xu, Chenxi; Ouyang, Gang; Xiao, Wuhan (Frontiers in Immunology, 2019)
Neddylation is a type of post-translational protein modifications, in which neural precursor cell expressed developmentally downregulated protein 8 (NEDD8) is covalently conjugated to the lysine residues of target substrates. The best characterized principal substrates of neddylation are the cullin-RING ligases (CRLs). In addition, neddylation also modifies non-cullin proteins to affect gene regulation, cell survival, organ development, and stress response. However, the role of neddylation in antiviral innate immunity remain largely unknown. Here, we found that when neddylation was blocked by the NEDD8 activating enzyme E1 (NAE) inhibitor, MLN4924, the cellular and organismal antiviral response was suppressed. Moreover, the disruption of nedd8 increased the sensitivity of zebrafish to SVCV infection. Further assays indicated that blocking or silencing neddylation significantly downregulated key antiviral genes after poly (I:C) stimulation or SVCV infection, but dramatically increased SVCV replication. Neddylation of Irf3 and Irf7 was readily detected, but not of Mda5, Mavs and Tbk1. Thus, our results not only demonstrated that neddylation facilitated the antiviral response in vitro and in vivo, but also revealed a novel role of nedd8 in antiviral innate immunity.